2000
DOI: 10.1523/jneurosci.20-16-05940.2000
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Ca2+-Dependent Signaling Pathways Regulate the Motor Output of Cochlear Outer Hair Cells

Abstract: The outer hair cells (OHCs) of the cochlea have an electromotility mechanism, based on conformational changes of voltage-sensitive "motor" proteins in the lateral plasma membrane. The translocation of electrical charges across the membrane that accompanies electromotility imparts a voltage dependency to the membrane capacitance. We used capacitance measurements to investigate whether electromotility may be influenced by different manipulations known to affect intracellular Ca(2+) or Ca(2+)-dependent protein ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
2
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 49 publications
5
89
2
3
Order By: Relevance
“…5C), suggest a common substrate. Antagonistic effects of W-7 and okadaic acid have been observed by Frolenkov et al (2000) using the cell membrane nonlinear capacitance measurement in an OHC preparation. These investigators however concluded that the primary substrate for this phosphorylation/dephosphorylation process was the electromotile mechanism.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…5C), suggest a common substrate. Antagonistic effects of W-7 and okadaic acid have been observed by Frolenkov et al (2000) using the cell membrane nonlinear capacitance measurement in an OHC preparation. These investigators however concluded that the primary substrate for this phosphorylation/dephosphorylation process was the electromotile mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…As yet there is no report demonstrating the presence of either MLCK or any CaMK in amphibian hair cells. However, immunological studies have suggested the presence of myosin light chain kinase in mammalian OHCs (Knipper et al, 1995), and have localized the Ca 2+ /CaM-dependent protein kinase IV in the OHC cytoplasm (Koyama et al, 1999;Frolenkov et al, 2000). ML-7 is a specific MLCK inhibitor (Saitoh et al, 1987;Bain et al, 2003), whose effects on the slow motility in OHCs have been previously reported (Puschner and Schacht, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 and 7), indicating that extracellular Ca ++ plays a key role in the effect of ATP on OHC electromotility. It has been hypothesized that Ca ++ modulates OHC electromotility via two pathways: modifying cytoskeletal stiffness [32] and shifting the voltage sensitivity of OHC electromotility [33]. The effect of ATP on OHC electromotility may follow the same concept, activating the P2x receptors allowing Ca ++ influxing to modify OHC electromotility.…”
Section: Extracellular Ca ++ Ions Are Required For Atp Regulation On mentioning
confidence: 99%